(untitled) (London Journal of Medical and Health Research, 2024)
Drug delivery through the skin offers distinct advantages, including bypassing the liver’s initial metabolism, maintaining consistent drug levels in the blood, and ensuring safety and adherence to treatment, which surpasses traditional oral or injectable methods. Microneedle technology has emerged as a revolutionary approach in this regard, offering enhanced delivery efficiency and patient acceptance. The main obstacle to transdermal administration, however, is the fact that only a small number of strong medications with optimal physicochemical characteristics can intercellularly and passively diffuse across skin barriers to reach therapeutic concentration using this method. Innovative strategies have been pursued to improve the drug’s skin penetration. Microneedles, a microscale physical enhancement technique, have expanded the spectrum of medications that may be delivered transdermally and intradermally. These microneedles are usually between 0.1 and 1 mm in length, offering a minimally invasive yet highly effective method for drug administration. This review discusses the challenges associated with microneedle based TDDS, including formulation issues, skin permeability, and manufacturing complexities.We highlight recent advancements in microneedle design, materials, and fabrication techniques, shedding light on their potential to overcome these hurdles. One may create solid, coated, hollow, or dissolvable microneedles using a range of materials, including silicon, stainless steel, and polymers. Despite extensive research, several obstacles hinder the long-term, cost-effective production, and effectiveness of microneedles for transdermal drug delivery. This analysis identifies gaps in production technology and reviews characterization techniques. Microneedles show promise in various applications, including medicine delivery, vaccination administration, illness diagnosis, and cosmetics, indicating their versatility and wide-ranging potential.